Front Cover: Modelling Photoionisation in Isocytosine: Potential Formation of Longer‐Lived Excited State Cations in its Keto Form (ChemPhysChem 21/2021). Issue 21 (5th November 2021) - Segarra‐Martí, Javier; Bearpark, Michael J.
Abstract : The Front Cover shows the ultrafast photoionisation of DNA canonical nucleobase cytosine and the slower ionization process in non‐canonical base isocytosine embedded within a DNA backbone. More information can be found in the Article by Javier Segarra‐Martí and Michael J. Bearpark .